The host of GRB 060206: kinematics of a distant galaxy - Thöne, C.; Wiersema, K.; Ledoux, C.; Starling, R.; de Ugarte Postigo, A.; Levan, A.; Fynbo, J.; Curran, Peter; Gorosabel, J.; van der Horst, A.; Llorente, A.; Rol, E.; et al. (EDP Sciences, 2008)
Context. GRB afterglow spectra are sensitive probes of interstellar matter along the line-of-sight in their host galaxies, as well as inintervening galaxies. The rapid fading of GRBs makes it very difficult to obtain spectra of sufficient resolution and S/N to allow forthese kinds of studies.Aims. We investigate the state and properties of the interstellar medium in the host of GRB060206 at z = 4.048 with a detailed studyof groundstate and finestructure absorption lines in an early afterglow spectrum. This allows us to derive conclusions on the natureand origin of the absorbing structures and their connection to the host galaxy and/or the GRB.Methods. We used early (starting 1.6 h after the burst) WHT/ISIS optical spectroscopy of the afterglow of the gamma-ray burstGRB060206 detecting a range of metal absorption lines and their finestructure transitions. Additional information is provided by theafterglow lightcurve. The resolution and wavelength range of the spectra and the bright afterglow have facilitated a detailed study andfitting of the absorption line systems in order to derive column densities. We also used deep imaging to detect the host galaxy andprobe the nature of an intervening system at z = 1.48 seen in absorption in the afterglow spectra.Results. We detect four discrete velocity systems in the resonant metal absorption lines, best explained by shells within and/or aroundthe host created by starburst winds. The finestructure lines have no less than three components with strengths decreasing from theredmost components. We therefore suggest that the finestructure lines are best explained as being produced by UV pumping fromwhich follows that the redmost component is the one closest to the burst where Nv was detected as well. The host is detected in deepHST imaging with F814WAB = 27.48 ± 0.19 mag and a 3s upper limit of H = 20.6 mag (Vega) is achieved. A candidate counterpartfor the intervening absorption system is detected as well, which is quite exceptional for an absorber in the sightline towards a GRBafterglow. The intervening system shows no temporal evolution as claimed by Hao et al. (2007, ApJ, 659, 99), which we prove fromour WHT spectra taken before and Subaru spectra taken during those observations.